The EFFECT OF APPLICATION MOBILE DISCHARGE PLANNING (MODSPLAN) TO INCREASING THE HOSPITAL READNESS IN ACUTE MYOCARDIAL INFARCTION - Megasari, Anis Laela (RSUP Dr. Kariadi, 2022)
BACKGROUND: Acute myocardial infarction is a disease that has a high recurrence rate. Discharge planning is an intervention that can be used to minimize the occurrence of repeated treatments. However, many reports state that the implementation of discharge planning is still not optimal. The use of inappropriate methods is the cause of the non-optimal implementation of discharge planning. This study proposes a new discharge planning method, namely the modisplan application OBJECTIVE: To increase the effect of the application of modisplan on optimizing discharge readiness in acute myocardial infarction patients. Not only that, this application is expected to improve the patient's ability to carry out continuity of care so that repeated treatments do not occur METHODS: The design used quasi-experimental with pretest-posttest nonequivalent control group design. Total respondent 30 were divided into the control group (15 respondents) and the intervention group. (15 respondents). The application of the Modis Plan application was carried out in a structured manner starting from assessment, management, monitoring and evaluation. Readiness to go home was measured using the Readiness of hospital discharge Scale questionnaire. The statistical test used the Wilcoxon test and the Independent T-Test. RESULTS: There is an effect of modisplan application to increasing the hospital readiness in acute myocardial infarction patien’s (p value 0.000). The final mean score in the control group was 114.73, while in the intervention group it was 134.80 CONCLUSION: The application of the modesplan application has been proven to optimize discharge readiness of acute myocardial infarction